The Effect Of Social Media Marketing Implementation Capability And Active Presence On Micro Enterprises’ Performance In Bandar Lampung - Muhammad Affan; Ayi Ahadiat; Nuzul Inas Nabila (Yayasan pendidikan dzurriyatul Quran, 2026)
The rapid development of digital technology and social media has transformed the way micro enterprises promote products, communicate with customers, and maintain business visibility. In Bandar Lampung, social media has become an important marketing channel because it provides an accessible, flexible, and relatively low-cost method to reach customers in an increasingly competitive market. However, many micro enterprises still face challenges in implementing social media marketing strategies effectively and maintaining consistent online activity. This study aims to examine the effect of social media marketing implementation capability and active presence on micro enterprises’ performance in Bandar Lampung. This research employed a quantitative explanatory approach using a non-probability purposive sampling technique. Data were collected through questionnaires distributed to micro-enterprise owners and managers, resulting in 105 valid responses. The data were analyzed using descriptive statistics, validity and reliability tests, and multiple linear regression analysis. The results indicate that social media marketing implementation capability and active presence have positive and significant effects on micro enterprises’ performance. Social media marketing implementation capability demonstrated a stronger statistical contribution than active presence. These findings suggest that micro enterprises need to combine structured social media marketing implementation with consistent active presence in order to improve customer relationships, market visibility, and overall business performance.